The challenges of COVID-19 in the Brazilian Amazonian communities and the importance of seroepidemiological surveillance studies - Antonio Carlos Rosário Vallinoto; Maria Karoliny da Silva Torres; Mariana Cayres Vallinoto; Izaura M. V. Cayres Vallinoto (BMC, 2020)
Abstract The emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has alarmed the world with its high rate of transmission and the ability to cause severe and fatal disease. The impact of this pandemic may be even greater in populations where the absence of health services is a chronic aspect, as reported with populations living in the Brazilian Amazon. In this article, we address the perspective of possible impacts of the pandemic on these populations and the importance of conducting seroepidemiological surveillance studies.